Performance of post-rainy (rabi) sorghum production technology under FLDs for enhancing productivity and profitability - Chapke, Rajendra R (Indian Farming, 2023)
Sorghum is mainly grown during rainy (kharif) and post-rainy (rabi) season. Post-rainy sorghum is mostly used for human consumption due to its good grain quality. Increasing productivity with improved cultivars based on soil conditions where rabi sorghum is grown on residual soils is of much importance in climate change scenario. Apart from the adoption of improved cultivationpractices, adoption of soil moisture conservation practices like deep ploughing, compartmental bunding or ridge and furrow method are beneficial in reducing water stress, improve yield and net returns compared to traditional practices. Total 3699 frontline demonstrations (FLDs) on rabi sorghum were organized in major sorghum growing areas of Maharashtra, Karnataka, Telanganaand Gujarat since 2012–13 to 2021–22 with improved rabi sorghum technologies which gave 49% more grain yield than the farmer’s practice (FP) and resulted into 49% more net returns.